FINANCIAL FEASIBILITY OF THE DAYAK NGAJU LUCK SALES BUSINESS (BUSINESS STUDY OF KACAPI TINGANG NGANDERANG IN PALANGKA RAYA CITY) - , Alen Setiawan; Wiratno (PARENTAS: Jurnal Mahasiswa Pendidikan Teknologi dan Kejuruan, 2023)
Central Kalimantan has various local cultures, especially Dayak arts in the form of Karungut, Sansana and Badeder. This art is generally accompanied by traditional musical instruments of the Dayak Ngaju tribe, namely the child lute (3 strings) and the main lute (2 strings), these musical instruments are made of jelutung wood (Dyera costulata). This artis generally played in collaboration between children's harps, main harps and various other Dayak traditional musical instruments. In line with the times, art and the existence of traditional musical instruments are increasingly being left out or left behind because modern musical instruments are considered apable of accompanying regional arts and modern musical instruments are considered more practical, and asier to play. One of the efforts made to be able to maintain the existence of the traditional lute musical instrument is by increasing enthusiasts and users of the lute musical instrument so that it is more often seen and known by the public. From this program, Kacapi Tingang Nganderang became a solution by running several sales, production, promotion and marketing programs for Dayak Ngaju lute musical instruments within the local community, especially in the City of Palangka Raya. In the business of selling lute by Kacapi Tingang ganderang, Financial Feasibility Study was carried out in order to determine whether or not a business selling the Dayak Ngaju lute was feasible. The Financial Feasibility Study was conducted at a location located at Jalan Tingang XV, Palangka Village, Jekan Raya District, Palangka Raya City, by collecting primary data and secondary data. Primary data is data obtained directly from business owners by means of observation or interviews, and secondary data is data obtained from other agencies related to research. Analysis of the data used in this study is "Financial Feasibility Analysis" in the form of analysis of NPV, BCR, IRR, and BEP with a MARR rate of 28.36%, which is obtained from a business opportunity rate of 8%, a business risk factor of 2%, bank loan interest regions 13% and the July 2021 inflation rate against July 2022 is 4.94%. These data are processed in the form of cash flows of 80 options which are divided into 2 groups, namely raw material price options that have remained unchanged for 5 years and raw material price options thathave increased based on an inflation rate of 4.94% and from the research conducted a conclusion is drawn. which states the results of a study. From this study, the results obtained stated that the business of selling the Dayak Ngaju lute by Kacapi Tingang Nganderang was declared financially infeasible with a percentage of 96% Unfeasible and 4% Eligible.